A POLITICAL EDUCATION RELATED TO DETERMINING THE PRESIDENTIAL TRESHOLD IN THE CANDIDATE FOR PRESIDENT AND VICE PRESIDENT IN INDONESIA - Mario Akbar Akroma; Riski Febria Nurita; Yusuf Eko Nahuddin (EDUCATUM: Scientific Journal of Education, 2023)
This research focuses on the political education about presidential threshold or the threshold of votes that a political party must obtain in an election to be able to nominate a presidential candidate. The presidential threshold regulates the minimum requirements for submitting presidential and vice presidential candidates, namely that 20% of the votes of a political party or combination of political parties must be obtained. To explore this study, the researchers formulated the problem as follows: What are the basic considerations in determining the 20% presidential threshold? With the aim of knowing and analyzing the basis for considering the 20% presidential threshold in selecting presidential and vice presidential candidates in Indonesia..The results of the research show that a. in consideration of determining the presidential threshold, it does not match the essence of its initial objectives, because it only benefits the majority party and in its preparation it is not in accordance with the aspirations of strengthening the presidential system and simplifying the party.